Investigation of Dust Emission Caused by Wind Erosion in Hormozgan Province - Mehdi Rahnama; Saviz Sehat; Sara Karami; Abbas Ranjbar; Noushin Khoddam (Nīvār)
In recent years, dealing with the phenomenon of dust has become one of the most important environmental challenges in different regions of the world, and many studies have been conducted in connection with the identification of sources of dust and the areas affected by them, as well as ways to deal with it. Iran, as one of the countries located in the global dust belt, is affected by the dust phenomenon, and its different provinces are involved in this phenomenon in different seasons. Hormozgan province, located on the northern shores of the Persian Gulf, is affected by dust events due to weather patterns. In this article, using different observational data, remote sensing products and numerical modeling, dust springs in Hormozgan province have been identified and the areas affected by them have been identified. The results showed that dust springs with intense activity are located in the southeast of Jask city, the border of Bandar Abbas and Khmer cities, and also east of Bandar Lange. The highest amount of vertical dust flux is related to Jask, south of Bandar Abbas, Bandar Khem and east of Bandar Lange, which also include the highest potential of dust with wind speed of 20 meters per second and humidity of 5%.